USING TEXT FROM THE BOOK SPINE AS A MARKER FOR AUGMENTED REALITY IN LIBRARY BOOKSHELF MANAGEMENT SYSTEM - Salin Boonbrahm; Charlee Kaewrat; Charoenporn Bouyam (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2017)
Looking for the book in the library may seem to be a hard work for patrons but in fact, it is even harder for librarians, who have to organize the book so that it is convenient for the patrons. Usually, when patrons took the books out from the shelf they tend to put them back to the shelves without seriously put them back exactly where they belong which cause problems to the next patrons who use OPAC searching for the book. So it is the job for the librarian to carefully check for misplacing books and this process is usually been done manually. To speed up the process, some researcher suggesting that Augmented Reality technology can do the job. Augmented Reality (AR) is the process of integrating computer generating objects and real-world environment. Since AR need the exact location to place the virtual object, these can be done by 2 techniques i.e. marker-based AR and markerless AR. Using the marker-based AR, the markers have to be created and attached to the books. For medium and large libraries, where there are more than half million books, this is a tedious work and need a lot of money. To avoid this situation, we have conducted an experiment in which the image on the book spine is used as a marker, so no need in attaching anything else on the book. Image processing technique is used to localize the call number on the book spine and optical character recognition is introduced to get the text out. These image and text are then used as a marker for AR. Results from the experiments showed that text on the book spine can replace markers for bookshelf management in the libraries